2015
DOI: 10.3892/mmr.2015.4232
|View full text |Cite
|
Sign up to set email alerts
|

Naringin ameliorates cognitive deficits via oxidative stress, proinflammatory factors and the PPARγ signaling pathway in a type 2 diabetic rat model

Abstract: Naringenin is a flavonoid polyphenolic compound, which facilitates the removal of free radicals, oxidative stress and inflammation. The present study aimed to obtain a better understanding of the effects of curcumin on the regulation of diabetes‑associated cognitive decline, and its underlying mechanisms. An experimental diabetes mellitus (DM) rat model was induced by streptozoticin (50 mg/kg). Following treatment with naringin (100 and 200 mg/kg) for 16 weeks, the body weight and blood glucose levels of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 55 publications
(50 reference statements)
3
24
0
Order By: Relevance
“…These results revealed the antioxidative stress effects of naringin. In fact, a few reports have revealed that naringin could ameliorate cognitive deficits by enhancing antioxidative stress [29,31], as demonstrated by our current results. In addition, our previous studies have observed that CCL2 can enhance NMDA receptor-mediated EPSC and mediate Ca 2+ influx [12,32].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results revealed the antioxidative stress effects of naringin. In fact, a few reports have revealed that naringin could ameliorate cognitive deficits by enhancing antioxidative stress [29,31], as demonstrated by our current results. In addition, our previous studies have observed that CCL2 can enhance NMDA receptor-mediated EPSC and mediate Ca 2+ influx [12,32].…”
Section: Discussionsupporting
confidence: 83%
“…9 Naringin improves CCL2-induced cognition impairment mechanism illustration. Naringin treatment inhibited the oxidation, inflammation, reducing excitotoxicity and ultimately alleviating neurons apotosis and damage in rats with learning and memory impairment [16,29]. Therefore, elevated SOD and GSH-Px activities could directly reflect a powerful antioxidative ability.…”
Section: Discussionmentioning
confidence: 98%
“…Naringin ameliorates sodium arsenite-induced renal and hepatic toxicity in rats by modulating the activities of KIM-1, caspase-3, TGF-β and TNF-α (Adil et al 2015). Naringin ameliorates cognitive deficits via oxidative stress, proinflammatory factors and the PPARγ signaling pathway in a type 2 diabetic rat model (Qi et al 2015). Naringin protects neural cells on 3-nitropropionic acid-induced mitochondrial dysfunction through modulation of Nrf2 signaling pathway (Kulasekaran and Ganapasam 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Oral administration of NG (10, 20, and 40 mg/kg) to isoproterenol exposed Wistar rats showed a considerable decrease in the levels of lipid peroxidation products and improved the antioxidant status [47]. NG is known for its anti-inflammatory [46,[48][49][50] and antioxidative nature [43,45,51,52]. Arsenic-induced hepatic and renal toxicity are reported to be reduced by anti-inflammatory and antioxidative nature of NG [53].…”
Section: Studies On Ameliorative Nature Of Ng Against Oxismentioning
confidence: 99%
“…An experimental diabetes mellitus rat model was induced by streptozoticin (50 mg/kg) and NG treatment (100 and 200 mg/kg) for 16 weeks was given. A Morris water maze test was used to analyze the effects of NG on the cognitive deficit, and the results demonstrated that NG ameliorated cognitive deficits through OxiS, pro-inflammatory factors, and the peroxisome proliferatoractivated receptor gamma signaling pathway in the Type 2 diabetic rat model [52].…”
Section: Effect Of Ng On Oxis In Diabetic Modelsmentioning
confidence: 99%